2016
DOI: 10.1007/s10620-016-4329-5
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Glial Cell Line-Derived Neurotrophic Factor Positively Correlates with Symptoms in Functional Dyspepsia

Abstract: Increased expression of duodenal GDNF might be involved in FD pathophysiology and symptom perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 21 publications
5
37
0
1
Order By: Relevance
“…80) are upregulated in duodenal biopsy samples of patients with functional dyspepsia. This finding is consistent with higher levels of GDNF in patients with functional dyspepsia 79 . Both duodenal and gastric biopsy samples showed mast cell hyperplasia and an increased release of histamine and tryptase (which indicates mast cell activation) 81 .…”
Section: Gastroduodenal Sensitivitysupporting
confidence: 87%
See 1 more Smart Citation
“…80) are upregulated in duodenal biopsy samples of patients with functional dyspepsia. This finding is consistent with higher levels of GDNF in patients with functional dyspepsia 79 . Both duodenal and gastric biopsy samples showed mast cell hyperplasia and an increased release of histamine and tryptase (which indicates mast cell activation) 81 .…”
Section: Gastroduodenal Sensitivitysupporting
confidence: 87%
“…Evidence for sensitization of peripheral nerves is prov ided by the observation that nociceptor-related genes that encode β-nerve growth factor, glial cell line-derived neurotrophic factor (GDNF) 79 and TRPV1 (REF. 80) are upregulated in duodenal biopsy samples of patients with functional dyspepsia.…”
Section: Gastroduodenal Sensitivitymentioning
confidence: 99%
“…Of the 10 studies that evaluated mast cell counts, 5 studies reported increased mast cell infiltration in the duodenum and 1 in the duodenal bulb. The pooled results showed increased duodenal mast cell counts (SMD = 0.66, 95%CI 0.20‐1.13, P = .005) in individuals with FD . There was heterogeneity observed among the studies ( I 2 = 82%, P < .001) but no publication bias was detected (Egger's test P = .833).…”
Section: Resultsmentioning
confidence: 88%
“…Nineteen studies examined eosinophil infiltration in FD. A pooled evaluation showed increased duodenal eosinophils in individuals with FD (SMD = 0.95, 95%CI 0.66‐1.24, P < .001) compared to controls (Figure A) . Although significant heterogeneity ( I 2 = 88%, P < .001) and publication bias (Egger's test P = .004, Figure B) were observed, no single publication was found to bias the results in the sensitivity analysis (Figure C).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation